Edible Mushrooms in The Surroundings of Bangbayang Village, Situraja, Sumedang, West Java - Qonitah, Tsabitah Athifah; Aryyanto, Muhammad Raul Alfadri; Suteja, Hardiansyah; Murti, Alena Puspa; Noverita, Noverita (Journal of Tropical Biodiversity, 2023)
Bangbayang is one of the villages located in the Situraja Subdistrict, Sumedang Regency, West Java. The natural conditions around the area are very cool with various types of plants, which also make it likely to find mushrooms, especially macro mushrooms that have the potential as food ingredients, but have not been reported. This study aims to inventory macro mushrooms with the potential as food ingredients in Bangbayang Village, Situraja Subdistrict, Sumedang Regency, West Java. The research method used is exploratory, and each sample of macro mushrooms obtained is observed based on the macroscopic characteristics of its fruiting body. The results of the study obtained a total of 12 species of macro mushrooms with the potential as food ingredients, namely; Agaricus campestris, Auricularia auricula, A. cornea, Boletus edulis, Cortinarius caperatus, Filoboletus manipularis, Lentinus sajor-caju, Lepista nuda, Russula rosea, Sarcomyxa edulis, Termitomyces clypeatus, and Tricholoma fraticum.